What price victory? - Weber, David, 1952-; Zahn, Timothy; Pope, Thomas, 1972-; Lindskold, Jane M.; Kotouč, Jan, 1987-; Presby, Joelle (Weber, David, 1952- Worlds of Honor, 2023)
"The hottest military science fiction series of all time continues. The mission: to boldly explore David Weber's Honorverse; to deliver all the action, courage, derring-do, and pulse-pounding excitement of space naval adventure with tales set in a world touched by the greatness of one epic heroine-Honor Harrington. New Honorverse tales by Timothy Zahn & Thomas Pope, Jane Lindskold, the Honorverse Czech translator Jan Kotouč, and Joelle Presby. Plus "First Victory," an all-new novella by David Weber!"--